Back squat potentiates both vertical and horizontal jump performance in collegiate ice hockey players - Bechtel, C.; Cotter, J. A.; Schick, E. E. (International Journal of Kinesiology & Sports Science, 2018)
Background: Back squats (BSQ) have been shown to transiently improve performance in explosive vertical movements such as the vertical jump (VJ). Still, understanding of this phenomenon, termed post-activation potentiation (PAP), remains nebulous as it relates to explosive horizontal movements. Objective: Therefore, the purpose of the present investigation was to assess whether heavy BSQ can potentiate both VJ and horizontal jump (HJ) performance. Method: Nine male ice hockey players from the Long Beach State ice hockey team performed five testing sessions separated by 96-hours. The first testing session consisted of a one repetition maximum (1-RM) BSQ to determine subsequent testing loads. The four subsequent testing sessions, which were randomized for order, consisted of five repetitions of BSQ at 87% 1-RM followed by horizontal jump (BSQ-HJ), five repetitions of BSQ at 87% 1-RM followed by vertical jump (BSQ-VJ), horizontal jump only (CT-HJ) and vertical jump only (CT-VJ). During the potentiated conditions, rest intervals were set at five minutes between the BSQ and either VJ or HJ. Alpha-level was set a priori at 0.05. Results: The results indicate that both vertical (p=0.017) and horizontal (p=0.003) jump were significantly increased (VJ= +5.51cm, HJ= +11.55cm) following a BSQ. Conclusion: These findings suggest that BSQ may improve both vertical and horizontal jump performance in athletes who participate in sports emphasizing horizontal power, such as ice hockey.